Zoological Surrealism : The Nonhuman Cinema of Jean Painlevé - Cahill, James Leo (Book collections on Project MUSE., 2019)
"This critical history examines the work of zoological and science film pioneers Jean Painleve and Genevieve Hamon from 1924-1949, illuminating the significant contributions that their wildlife cinema made to philosophical and political thought"--